The Influence of Corner Care Using Topical Breast Milk and Dry Gauge Methods on The Time of Crap Delivery - Febry Mutiariami Dahlan; Nurul Husnul Lail; Sarifatul Ma’rifah (KHD-Production, 2023)
The best umbilical cord care after birth is a controversial issue. Neonatal tetanus cases in Indonesia increased from 10 cases in 2018 to 17 cases in 2019, While in Banten Province in 2019, there were 12 cases of neonatal tetanus with 8 deaths, including in Cilegon City. According to research, one of the preventions of neonatal tetanus is umbilical cord care. This study aimed to analyze the effect of umbilical cord care by using the breast milk topical method and dry gauze when removing the umbilical cord. This research is a quantitative study with a quasi-experiment research design with a control design post only, the sample is 30 respondents with a purposive sampling technique, and the research instrument is in the form of an observation sheet. The data were analyzed with an independent T-test. The results of a bivariate analysis can be concluded that there is a significant effect between differences in the acceleration of umbilical cord release. In this study, there was a significant difference between umbilical cord care using the topical method of breast milk and dry gauze on the timing of umbilical cord detachment. This can be input and evaluation for PMB in Cilegon City, regarding the importance of effective newborn umbilical cord care and does not cause infection.